Каркасні підходи у стратегії управління територіями - Дишлик, Олександр Петрович; Чабанюк, Владислав (НУБіП України, 2024)
В статті представлена теза доповіді учасника V Міжнар. наук.-практ. конф. «Формування сталого землекористування: проблеми та перспективи» 19 грудня 2024 р. м. Київ

As a specific strategy for using geographic information systems and technologies (GIS) for territorial management, the use of the so-called “AtlasSF Framework Approach” is proposed. It is a generalization of the AtlasSF Atlas Solutions Framework, which was previously used as a method and means of creating (classical) Atlas Systems (ATS). The AtlasSF Framework Approach as a strategy is a hierarchy of three homogeneous Decision Framework methods. They are called, respectively, the General (γ), Conceptual (β), and Application (α) Framework Solutions. The paper considers all three (γ, β, and α) Framework Solutions in the context of the current project in Ukraine to create the National Geospatial Data Infrastructure (NGDI).
Keywords: геоінформаційні системи; каркасний підхід AtlasSF; дуaлізм; ωПатерни; geographic information systems; AtlasSF frame-based approach; dualism; ωPatterns